A Classification of Thai Urban Public Spaces: A Case Study of Bangkok Metropolitan Area, Thailand - Kongphunphin, Chompoonut; Iamtrakul, Pawinee (Journal of Architectural/Planning Research and Studies (JARS), 2020)
Public spaces are one of the most important social components of the city which have been used to support human activities from the past to the present. At the same time, public spaces can help to reflect the physical characteristics of its surrounding that can identify the unique neighborhoods of each area. Nonetheless, it is not clearly shown in the Thai context. This research aimed to classify urban public space in Thai context by using Bangkok as a study area. The study method is an applying Geographic Information System (GIS) technique for analysis four main factors including urbanity, creativity, identity and sustainability. The results revealed that Thai urban public spaces can be classified into five types according to different contexts influencing roles and pattern of space utilization including; 1) Urban public space located in the city center with main characteristics of access and convenience that can serve various activities and user groups; 2) Community public space representing community location features originated by clustering sub-components of Thai society such as residence, institution and religious place; 3) Public space in the old town district positioned in the traditional district as the first community settlement area or city center in the past; 4) Open public space considered as urban infrastructure with characteristic of large-scale open area spreading across the community; 5) Public space in the sub-center located outside the city with outstanding characteristics of providing convenient lifestyles for residents in the surrounding areas.